Effect of recombinant bovine somatotropin (rbST) treatment on follicular population and development in non-lactating dairy cows - Rincón, Joao Alveiro Alvarado (Anim Reprod, 2019)
The aim of this study was to evaluate the long-term effects of recombinant bovine somatotropin (rbST) on follicle population and ovulatory follicle development in non-lactating dairy cows. Twenty-one Jersey cows were allocated in rbST (n=11) or control (n=10) groups. On day -60, cows in rbST group received 500 mg of somatotropin (s.c. Lactotropin®, Elanco). On day 0, control and rbST cows received an intravaginal progesterone-releasing device (1.9 g, CIDR(®), Zoetis) and GnRH (100 mg, IM, Factrel(®), Zoetis). On day 8, cows received PGF2α (25 mg, IM, Lutalyse®, Zoetis) and the CIDR(®) was removed. Twelve hours after device removal (D8), serum, follicular fluid and granulosa cells samples were collected. Serum and follicular concentration of estradiol (E2) and progesterone (P4) were analyzed. Total RNA was extracted from granulosa cells to measure gene expression of LHCGR, STAR, HSD-3B1, CYP11A1, CYP19A1, CYP17A1, IGFR and PAPPA by real-time PCR. Ultrasonography was performed on days -60, -53, -46, -14, -7, 0 and 8 for antral follicle count. Results were analyzed by repeated measures ANOVA and t-test. There was no effect of rbST treatment on the number of follicles during the 60 days period, as well as no effect on serum and follicular fluid E2 and follicular fluid P4 at the moment of follicle aspiration. There was a reduction in PAPPA (P = 0.006), CYP11A1 (P = 0.04) and CYP19A1 (P = 0.002) mRNA levels in granulosa cells of the pre-ovulatory follicle of rbST treated cows. In conclusion, a single dose of rbST did not have long-term effects on antral follicle population, serum and follicular E2/P4 concentrations in non-lactating dairy cows. Despite that, rbST injection decreased granulosa cell expression of genes related to steroidogenesis in the pre-ovulatory follicle.